ASSOCIATION OF AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE AND ABDOMINAL AORTIC ANEURYSM - Shterjova Markovska, Zh; Rambabova Bushljetikj, I; Severova, G; Trajcheska, L; Nikolov, I; Karanfilovski, V; Sulejman S; Usprcov J; Janevski, Z; Canevska, A; Karanfilovikj A; Krstevska Balkanov, S; et al. (My University, 2024)
ASSOCIATION OF AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE AND ABDOMINAL AORTIC ANEURYSM Z. Shterjova Markovska1, I. Rambabova Bushljetikj1, G. Severova1, L. Trajcevska1, I. Nikolov1, V. Karanfilovski1, S. Sulejman1, J. Usprcov1, Z. Janevski1, A. Canevska1, A. Karanfilovikj1, S. Krstevska Balkanov2, G. Spasovski1 1University clinic of Nephrology, 2University clinic of Hematology, Faculty of Medicine, University Sts. Cyril and Methodius Skopje, N. Macedonia PP Introduction. Autosomal dominant polycystic kidney disease (ADPKD) is a systemic disease with multiple cysts in several organs. Formation of aneurysms of: the aorta, coronary and cerebral arteries are increasingly reported in the literature as extra-renal manifestations. Case report. We report 77-year-old male with ADPKD and long-standing hypertension, admitted to our ward due to extreme weakness, malaise and abdominal pain with severe anemia and elevated serum levels of creatinine and urea. Treatments with hemodialysis and blood substitution were started. Abdomen echo-sonography showed hepatic cysts and polycystic kidneys. The cysts were filled with clear content, in the right kidney toward the upper pole, two larger cysts were notified and next to them а pulsatile cystic lesion was noted with hemorrhagicfilled content which was highly suspicious for an aneurismaticlly dilated abdominal aorta. CT angiography of the aorta showed dilated, tortuous aorta with advanced atherosclerosis along its entire length. The dilatation was evident in the descending part of the aorta, with infrarenal saccular dilatation before the bifurcation, that seemed to be thrombosed and next to it denser content was observed, probably older hemorrhagy, without imaging signs of acute extravasation of the contrast. Cardiovascular surgeon recommended coronography and coronary artery aneurisms were excluded. Unfortunantly the patient started to alternete with his consuosnes and brain CT angiography showed corticoreductive changes, no aneurism, extra-or intra-axial hemorrhage were observed. Due to the severe general condition, clinical assessment and advanced age of the patient, the case was declared as inoperable. Conclusion. Due to hypertension and associated connective tissue disorders patients with ADPKD are prone to develop aortic aneurysms, and should be questioned as a frequent feature in such patients, hence early diagnosis and treatment decisions based on a risk–benefit analysis, remains the cornerstone of management.
Keywords: POLYCYSTIC KIDNEY DISEASE; AORTIC ANEURYSM